Biomass, Oil and Fatty Acids Profiling Of Mangrove-Isolated Microalgae Under Selected Cultivation Conditions - Nur Syazana Binti Fauzi
Microalgae have been recognized for their substantial amount of oil content along with high long-chain marketable polyunsaturated fatty acids (PUFAs) such as omega-3 and -6 fatty acids. However, indigenous microalgae in Malaysia are mostly untapped resources for lipid assessment due to lack of research conducted, in particular the species from mangrove environment. Therefore, eight new mangrove-isolated microalgae species were successfully described through morphological characterization and molecular identification with 18S rDNA. The identified strains include the species from the genus of Chlorella, Desmodesmus, Chlamydomonas and Scenedesmus. In order to screen these species for potential oil and fatty acid productions, a small-scale cultivation system and an optimized oil extraction protocol were established. This enable cost-saving in term of reduce chemicals usage by 50% and increase efficiency from time-saving. The eight newly characterized species together with two model species (Chlorella vulgaris UMT-MI and Messastrum gracile SE-MC4) were subjected to nitrate-replete and nitrate-deficient cultivation conditions and its growth, biomass, oil content and fatty acid composition were determined. Result revealed that the microalgae could be categorized into high cell growth with high biomass (Group I), moderate cell growth with wider range of biomass (Group 11), and degrading cell growth with low biomass (Group III). Interestingly, five strains (UMT-Ml, SE-MC4, KS-2, UMT-B13 and UMT-B15) were regarded as oleaginous microalgae as they produced more than 20% (in between 23.5• 37.0%) of total oil content under the studied conditions. Furthermore, fatty acid profiling revealed that six strains (UMT-B8, -B13, -B14 and -B15, UMT-MI and KS- 2) were high saturated fatty acid (SFA) producers (or Group H-SFA) with total SFA ranging between 52.4-97.1%. Three strains (SE-MC4, UMT-B10, -B20) were high SFA and monounsaturated fatty acid (MUFA) producers (or Group H-SFA: MUFA) with each constituted more than 30% while one high producer (UMT-B11) for SFA and polyunsaturated fatty acids (or Group H-SFA: PUFA) with each constituted more than 30%. In addition, the influence of different growth phases and culture transition phase on the selected species, M. gracile SE-MC4 were also evaluated. Results showed that the biomass and total oil content increased in parallel to the cultivation day and achieved maximum at late stationary phase (day 8). This species accumulated high amount of Cl 8: 1 (32.4%) at late stationary phase and dropped instantaneously to 13% during the culture transition into Stage II cultivation. This was in contrast to the accumulation of Cl 8:3n3, where its content spiked up from a lowest to a maximum of 23.0%. These demonstrated that the storage Cl8:l pool in the late stationary phase was immediately used as a substrate for the synthesis ofC18:3n3 which could play an important role during the early phase ofmicroalgae growth. The mangrove microalgae can be looked up as a new prospective of lipids and fatty acid sources for various different applications. Understanding the biochemical properties of interest under specific stage of growth is important for future fundamental study to formulate further experiment that could increase the lipid content without compromising its biomass.